2023
DOI: 10.1520/jte20220487
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Micro, Nanocrystalline Cellulose and Textile Fibers from Coffee Waste

Abstract: Because of the environmental footprint of oil-based materials, the demand for bio-based renewable materials is hiked. The usage of agricultural waste to extract cellulose, minimized the dependent of hydrocarbon products which is an added value besides due to overpopulation the productivity is increased, which leads to an increase in agricultural waste that causes environmental pollution. In this work, various cellulosic materials, such as cellulosic textile fibers (CTF), microcrystalline cellulosic fibers, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Recent research provides further evidence supporting the removal of 91% of color from the Banana stem [136]. Some of the resent studies confirms that the waste extraction from coffee waste shows promising adsorbents for the dyes [137].…”
Section: Sustainable Wastewater Treatment For the Remediation 41 Bioa...mentioning
confidence: 71%
“…Recent research provides further evidence supporting the removal of 91% of color from the Banana stem [136]. Some of the resent studies confirms that the waste extraction from coffee waste shows promising adsorbents for the dyes [137].…”
Section: Sustainable Wastewater Treatment For the Remediation 41 Bioa...mentioning
confidence: 71%
“…Additionally, obtaining the beverage generates spent coffee grounds. These other by-products have been widely explored for revalorization, such as obtaining nanocellulose, with good outcomes (Alghooneh et al 2017;Dao et al 2022;Zeleke et al 2022;Shi et al 2021;Kanai et al 2020;Karunakaran et al 2023). Nevertheless, CP is poorly utilized, and its main usages are focused on energy production or as livestock feed additives, which do not represent value-added uses, evidencing a lack of revalorization of this by-product (Rodríguez Valencia and Zambrano Franco 2010;Franca et al 2009;Limousy et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, CP is poorly utilized, and its main usages are focused on energy production or as livestock feed additives, which do not represent value-added uses, evidencing a lack of revalorization of this by-product (Rodríguez Valencia and Zambrano Franco 2010;Franca et al 2009;Limousy et al 2017). On the other hand, it has been reported that CP has a high content of cellulose, ranging from 40 to 49% (Bekalo and Reinhardt 2010), which is interesting, since other coffee by-products have lower cellulose contents, ranging from 12 to 34% and have been successfully used for obtaining cellulose (Ballesteros et al 2014;Karunakaran et al 2023;Bekalo and Reinhardt 2010) making the CP a promising cellulose source.…”
Section: Introductionmentioning
confidence: 99%
“…The extracted fibers have environmental benefits such as biodegradation, and a reduction in carbon dioxide emissions, which are the main contributors to global warming. After oil, coffee is the most traded commodity in the world [20,21]. The method of separating the coffee bean results in a substantial amount of biowaste (i.e., coffee husk), the vast majority of which is simply thrown in landfills [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the coffee husk is a suitable biomass source for cellulosic fiber components. The extracted husk presents exciting opportunities to produce a variety of value-added products, including short textile fibers, fillers in composite materials, micro-and nano-scale materials such as micro and nanocrystalline cellulose, micro and nano fibrillar cellulose, the paper industry, and sorbent materials to remove hazardous substances [21].…”
Section: Introductionmentioning
confidence: 99%